2017
DOI: 10.4172/2155-9910.1000233
|View full text |Cite
|
Sign up to set email alerts
|

Enhance Growth and Biochemical Composition of Nannochloropsis oceanica, Cultured under Nutrient Limitation, Using Commercial Agricultural Fertilizers

Abstract: Microalgae culture media should be economic, allow for high growth, satisfy the needs of microalgal cells and easy to prepare. In this study, we evaluate the effect of different media formula prepared from commercial agricultural fertilizers (CAGF), comparing to F/2 Guillard standard medium as a control medium, on growth (cell density, CD; dry weight, DW and specific growth rate, µ) and biochemical composition (lipid, protein, and carbohydrate) of Nannochloropsis oceanica. Comparing to N/P ratio (9.6) and actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…Matta et al [72] cited that the lipid content of A. platensis ranging from 4 to 16%. However, the differences between our results and those obtained by other studies, even those isolated from the same site of El-Khadra Lake, may be due to different culture systems, scales, extraction methods, environmental conditions [21,36,37,[68][69][70][71][72][73], or available nutrient limitation [73].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Matta et al [72] cited that the lipid content of A. platensis ranging from 4 to 16%. However, the differences between our results and those obtained by other studies, even those isolated from the same site of El-Khadra Lake, may be due to different culture systems, scales, extraction methods, environmental conditions [21,36,37,[68][69][70][71][72][73], or available nutrient limitation [73].…”
Section: Discussioncontrasting
confidence: 92%
“…The aquatic organisms are a sustainable source of PUFA, MUFA, SFAs, palmitic acid, and fatty acid methyl esters [74,75]. Among all aquatic organisms, microalgal cells are the most sustainable, attractive, and promising source [1][2][3][17][18][19][20]69,72,73]. Cohen [76] stated that about 50 percent of the total lipid of Arthrospira is fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Marine algae are considered very important bioindicator for the marine ecosystem [13][14][15]. Many studies have reported that the constituents, diversity, and communities of marine algae are affected by variations in environmental parameters and nutrient limitation [65][66][67][68][69][70]. During the last few years, the attention on scientific and commercial interest to biotechnological applications of algae as a sustainable source and global commercial for aquaculture [71][72][73][74][75], biofuel [12,76], extracts [77,78], food supplement, pharmaceuticals, and cosmetics were increased [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, our data is in the same line of the results presented by Khairy and El-Shafay [13] who found that, during spring season of 2010, the highest component is carbohydrate (50.49%), followed by protein (23.72%) and lipid (2.71%). Many authors reported that the biochemical constituents of marine algae are affected by variations in environmental conditions and nutrient availability [65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%